Cytotoxic Activity of Gude Leaves (Cajanus cajan) using The Brine Shrimp Lethality Test (BSLT) Method - Emelda, Andi; Hasnaeni, Hasnaeni; Ulfa, Amanda (Universitas Pendidikan Mandalika, 2024)
Gude Leaves (Cajanus cajan) are a traditional medicinal plant for treating diarrhea. The ingredients contained in Gude leaves are flavonoids, such as kajanol, quarcetin and luteolin and also contain other secondary metabolites, tannins, saponins, alkaloids, terpenoids and phenols. Scientifically, Gude leaves have antimalarial, antidiabetic, anthelmintic, antioxidant, antibacterial and anticancer activity. This research aims to determine the toxicity of gude leaves (C. cajan) using the Brine Shrimp Lethality Test (BSLT) method. This research began by carrying out two extraction methods, namely maceration and UAE (Ultrasonic Assisted Extraction) on samples of gude leaves using 70% ethanol solvent. Then a phytochemical screening was carried out which showed that samples of gude leaves contained alkaloids, flavonoids, steroids, saponins and tannins. Experimentation the toxicity of gude leaf extract using maceration and UAE methods on Artemia Salina Leach larvae, each divided into 5 test groups, namely 4 treatment groups (concentrations of (250 ppm,Â LC=23,33% & 33,33%) ; (500 ppm, LC= 56,67% & 60%); (750 ppm, LC= 70% & 73%); and (1000 ppm, LC= 80%) and 1 positive control group (sea water ). The research results can be seen through probit analysis by calculating the LC50 value. The LC50 value of gude leaf extract using the maceration method was 242.52 and the result of gude leaf extract using the UAE method was 394.16 (Toxic). Â This research provides information regarding the toxic effects of gude leaf extract.